Randomization Among: The Other Randomization - Barnbaum, Deborah R. (Ethics & human research, 2019)
A valid informed consent process for a randomized controlled trial requires the disclosure to potential participants that they will be randomized to receive the study intervention or a control intervention. This is a case of randomization within a trial, a type of randomization that has received significant attention in research ethics. When institutions recruit large numbers of research participants for multisite clinical trials, a different, hidden form of randomization may occur: randomization among clinical trials. If it is essential to disclose to potential participants randomization within a clinical trial, then it may be the case that randomization among clinical trials recruiting individuals from the same cohort of eligible participants should also be disclosed. This article examines how randomization among clinical trials might take place and the ethical issues such randomization raises about informed consent to research participation.